Imaging-based characterization of cardiometabolic phenotypes focusing on whole-body MRI: an approach to disease prevention and personalized treatment - Gatidis, Sergios; Schlett, Christopher L.; Notohamiprodjo, Mike; Bamberg, Fabian (British journal of radiology, 2016)
Metabolic syndrome and cardiovascular disorders pose a challenge to global healthcare systems. Too often, patients with metabolic syndrome are diagnosed in advanced disease stages, where disease-associated damage is irreversible and treatment options are limited. Thus, prevention plays an increasingly important role in the management of cardiometabolic disorders. The main challenge of prevention is to identify patient groups who are at risk for developing overt disease and who might benefit from early therapeutic intervention. In this context, imaging-based phenotyping can add significant information to clinical evaluations, revealing anatomical and physiological changes that reflect intrinsic and extrinsic risk factors. The purpose of this review article was to provide an overview of the current state of imaging-based phenotyping of metabolic syndrome and cardiovascular disorders and to discuss current and potential developments in this field.
Gesehen am 14.05.2020